2018
DOI: 10.1007/s00256-018-2944-2
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided biopsy in suspected spondylodiscitis: microbiological yield, impact on antimicrobial treatment, and relationship with outcome

Abstract: PurposeTo investigate the clinical impact of CT-guided biopsy, as performed in routine clinical practice, in patients with suspected spondylodiscitis on MRI in terms of culture yield, impact on antimicrobial treatment, and outcome.MethodsThis study included 64 patients with MRI findings compatible with spondylodiscitis who underwent CT-guided biopsy.ResultsInitial CT-guided biopsies were culture-positive in 20/64 (31.3%, 95% confidence interval [CI] 21.2–43.3%). Repeat CT-guided biopsies (after initial negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…As our results demonstrate, none of the tested parameters independently predicted a positive finding of microbiological analysis. Kasalak et al 1 analyzed different clinical, radiological and laboratory parameters including leucocytes and C-reactive protein in order to find differences between culture positive and culture negative CT biopsy specimen. None of their analyzed parameters was significantly different between both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our results demonstrate, none of the tested parameters independently predicted a positive finding of microbiological analysis. Kasalak et al 1 analyzed different clinical, radiological and laboratory parameters including leucocytes and C-reactive protein in order to find differences between culture positive and culture negative CT biopsy specimen. None of their analyzed parameters was significantly different between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious spondylodiscitis is a relatively rare disease with an estimated incidence of about 0.4 to 2.4. per 100.000 in Europe. 1 Over the past years an increasing incidence has been described, 2 which might be attributable to earlier and more sensitive diagnostic procedures as well as a rising proportion of immunocompromised patients in hospitals. 3-5 Early diagnosis and treatment are mandatory, as the disease might be lethal in up to 17% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Gul et al [10], the success rate was found to be 80% and the only factor that had a significant relationship with success was reported as lesion histopathology. In a recent study by Kasalak et al [11], which included 64 patients with suspected spondylodiscitis, only 31.3% had culture positivity. However, 96.9% of culture positive patients were treated appropriately.…”
Section: Discussionmentioning
confidence: 94%
“…However, 96.9% of culture positive patients were treated appropriately. Therefore, the importance of biopsy has been emphasized in guiding the treatment [11]. In the meta-analysis performed by Pupabiool et al [12], the sensitivity and specificity of the imaging-guided biopsies performed for spontaneous vertebral osteomyelitis were reported as 52.2% and 99.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Endeavors to identify both clinical variables and imaging features predictive of microbiological pathogen detection in spondylodiscitis patients have been undertaken by several studies [6,8,15,16,21]. However, results were, in part conflicting and there still exists no consensus in the issue.…”
Section: Discussionmentioning
confidence: 99%